Length-weight relationship and condition factor of fish populations in Temengor Reservoir: indication of environmental health - Muzzalifah Abd Hamid,; Mashhor Mansor,; Siti Azizah Mohd Nor, (Universiti Kebangsaan Malaysia, 2015)
Length-weight relationship (LWR) and condition factor of seven fish species from the Temengor Reservoir, Peninsular Malaysia were analyzed. A total of 1155 individuals belonging to two families namely Nandidae and Cyprinidae were measured and weighed. The most highly represented family was Cyprinidae which comprised six species. Among these seven species, three species generally showed positive allometric growth, two species showed isometric growth and the other two species showed negative allometric growth. The exponent b value of LWR ranged between 2.601 (Oxygaster anomalura) and 3.157 (Cyclocheilichthys apogon) with a mean of 2.983. The lowest mean condition factor, K was recorded in O. anomalura (0.648 ± 0.131) while the highest value was observed in Pristolepis fasciata (2.194 ± 0.153). This study has contributed to the knowledge of fish populations in this economically important area that could assist fishery management scientists in carrying out future ecological studies in line with the strategies of conservation, restoration and management.